Counter Culture: The Making of Feminist Food in Feminist Restaurants, Cafes, and Coffeehouses - Ketchum, Alexandra (Cuizine, 2016)
Self-identified feminist restaurants and cafes of the 1970s and 1980s in the United States and Canada acted as spaces that challenged the status quo around cooking and consumption through their creation of feminist food. Each restaurant and cafe defined “feminist food” differently depending on the particular feminist ethics of the restaurant owners. Depending on the restaurant, making their food feminist revolved around vegetarian ethics, labour issues, cost, and sourcing of products. By looking at what was included and banned on these restaurant menus, this article shows the ways that food could be labelled as feminist. Furthermore, this piece demonstrates how one could assert feminism within a business dedicated to food—one in which complex relationships with the kitchen can also be analyzed (the kitchen being often labelled a "traditional" place for women).